Pulmonary Hyalinizing Granuloma Mimicking Metastatic Lung Cancer - Nuri Düzgün; Ercan Kurtipek; Hıdır Esme; Meryem İlkay Eren Karanis; İsmet Tolu (Case Reports in Pulmonology)
Pulmonary hyalinizing granuloma is a very rare benign condition, which usually manifests as solitary and sometimes as multiple pulmonary nodules. Deposition of immune complexes in the lung parenchyma due to hypersensitivity reactions is implicated in the etiology of pulmonary hyalinizing granuloma. A 59-year-old female patient who presented to our clinic with complaints of chest pain and cough had bilateral, multiple, and rounded lesions with regular margins suggesting metastatic lung disease. A transthoracic needle biopsy of the nodule was performed in the left pulmonary anterior segment. Biopsy showed no malignancy. Since no diagnosis was made by the biopsy, the patient underwent a video-assisted thoracic surgery. The wedge biopsy reported pulmonary hyalinizing granuloma. We aimed to present the diagnosis and treatment stages of our patient who was diagnosed with pulmonary hyalinizing granuloma in the light of literature review.